ANALISIS ANOMALI SINYAL ULTRA LOW FREQUENCY BERDASARKAN DATA PENGUKURAN GEOMAGNETIK SEBAGAI INDIKATOR PREKURSOR GEMPABUMI WILAYAH LAMPUNG TAHUN 2016 - Ulfa Wahyuningsih; Syamsurijal Rasimeng; Karyanto Karyanto (Jurnal Geofisika Eksplorasi, 2018)
Regional research had been done to analysis anomalies signal of ultra low frequency based on measurement data as an indicator of the geomagnetic earthquake precursor of lampung in 2016. To achieve purpose of the study conducted by the following steps: (i) Calculation of the total magnetic field of data; (ii) Daily Trend Analysis; (iii) the Fourier transform of the data Geomagnetic Anomaly; (iv) Localization Frequency ULF; (v) Calculation of Ratio Vertical-Horizontal (Polarization Ratio Z / H); (vi) Correction magnetic storms or Disturbance Strom Time (DST); (vii) the identification of earthquake precursors; (viii) Determination of OnsetTime, leadtime,and the direction of precursors. The results of the analysis of ten earthquakes with a magnitude above 5 MW have precursors between 11 to 30 days before an earthquake. Nine out of ten earthquakes studied had an earthquake precursors and precursors that do not have, this is because the distance is too far from the station Magdas in Liwa, West Lampung. Thus it can be seen that the precursor using the magnetic data can be used to make short-term predictions.